The influence of influencer marketing and product ratings on consumer trust at Shopee : a study of Shopee generation Z users - Tri Ahmad Hilal Rahmatulloh; Putra, Syaifurrizal Wijaya (Proceeding of International Management Conference and Progressive Papers, 2024)
The growth of e-commerce has driven the role of digital marketing as a key tool in building consumer trust, especially among generation Z who are highly influenced by consumer reviews and influencers on social media. This study aims to analyze the influence of influencer marketing and consumer reviews on consumer trust on the Shopee platform, with a focus on generation Z users. This study used a quantitative approach with a survey method, involving 110 respondents selected using purposive sampling technique. Data was analyzed using multiple linear regression with a questionnaire using a Likert scale. The results of this study showed that both influencer marketing and consumer reviews significantly positively influence consumer trust, with influencer marketing having a stronger influence than consumer reviews. This study makes an important contribution to the digital marketing literature by revealing the most influential factors in building consumer trust among generation Z on e-commerce platforms. The practical implications of these results suggest the importance of collaboration strategies between e-commerce and influencers as well as improving the quality of product reviews to increase consumer trust. This research is expected to serve as a basis for further research exploring the dynamics of consumer trust in the digital era.